Climatic conditions and human activities shape diploid–tetraploid coexistence at different spatial scales in the common weed Tripleurospermum inodorum (Asteraceae). (4th June 2019) - Čertner, Martin; Kúr, Pavel; Kolář, Filip; Suda, Jan
Abstract: Aim: While environmental conditions are reported as important determinants of cytotype distribution patterns in some mixed‐ploidy plant species, in others they seem to play no role. One reason for such inconsistency might be how and at what spatial scale the ecology of different cytotypes is compared. To address this issue, we adopted several complementary approaches to assess ecological requirements of cytotypes in a single species across wide‐range of spatial scales. Location: Europe. Taxon: Tripleurospermum inodorum (Asteraceae). Methods: WorldClim extracted data were used for comparing climatic niches of T. inodorum diploids and tetraploids at continental and subcontinental scales and for predicting climatic suitability of habitats in Europe. Within the contact zone of cytotypes, at the regional scale, ecological preferences of cytotypes were assessed independently in three regions. Habitat types and ecological indicators inferred from species composition of vegetation in both uniform‐ploidy and mixed‐ploidy populations were used for ecological niche reconstructions. Results: The two cytotypes differed in their climatic niches. However, due to considerable niche overlap, diploids and tetraploids were predicted to co‐occur in an extensive contact zone in Europe. Within the contact zone, cytotypes had identical ecological preferences but varied in their frequency at particular habitat types. The ecological niches of mixed‐ploidy and uniform‐ploidy populations were undistinguishable. Main conclusions: Cytotype distribution patterns may be shaped by multiple environmental forces, each operating at a different spatial scale. In T. inodorum, climate is an important driver of cytotype distribution patterns at continental scale, however, at finer scales within the contact zone, the founder effect and non‐random migration patterns caused by human activities seem to be more important than environmental heterogeneity. The use of independent replicates and/or across‐scale comparisons can significantly improve the performance of ecological niche assessments.